The Impact of the Care Equity Project with Community/Public Health Nursing Students - Kamau-Small, Sylvia; Joyce, Barbara; Bermingham, Neysa; Roberts, Jada; Robbins, Curtis (Public health Nursing, 2015)
Objective The purpose of this article is to report on the evaluation process of a multi‐disciplinary interactive teaching‐learning workshop implemented in a college of nursing baccalaureate program. Design and Sample A 6‐hr workshop on cultural humility and care equity was implemented using educational theater to bring clinical situations involved in community/public health practice into the classroom. One hundred and forty‐nine students participated in the workshop. Stages of Change (Prochaska and DiClemente [2005] Handbook of psychotherapy integration. New York: Oxford University Press) and the Learning Transfer Barriers Framework (Price, Miller, Rahm, Brace, & Larson [2010] Journal of Continuing Education in the Health Professions, 30, 237–245.) provided conceptual underpinnings for project evaluation. Measures Nursing students completed a quiz, postworkshop online surveys at 2 and 8 weeks, and a clinical application report (CAR). Survey data provided information on barriers to the transfer of knowledge from theory class to the clinical setting. Qualitative methods were used to audit the CARs. Each CAR was independently reviewed to determine the Stage of Change reflected in the narrative. Results Workshop evaluation outcomes provide evidence that cultural humility skill building has created behavior change in clinical practice for new health care community/public health nursing providers.